Analisis Perencanaan Pajak Penghasilan Terkait Dengan Beban Pajak Penghasilan Pasal 21 Yang Ditanggung Perusahaan Studi Kasus Pada PT. Kharisma Buana Mandiri - Poere, Daniel De; ., Stevanie (Institut Bisnis dan Informatika Kesatuan, 2016)
Tax planning is a legally used method by companies to save its tax payment. Income tax planning article 21 is a tax planning applied based on employee’s salary. It is an expense borne by companies and will disserve the company due to its inability to be made deductible fiscal expense. The research’s objective is to find out the influence of income tax planning related to article 21 borne by the company with gross up methode. The results conclude that the company does not use gross up method in calculationg its article 21 income tax. This is why the author made a revsion the fiscal income statement used in previous calculation. Based on this revision, the company will be able to save Rp 1.665.028 obtained as a difference between fiscal correction on article 21 tax expenses and the increase of article 21 tax income after being grossed up. This means the company can save its expenditure.